2-CF3-PEAI to eliminate Pb0 traps and form a 2D perovskite layer to enhance the performance and stability of perovskite solar cells. (May 2022) - Zhou, Junjie; Li, Minghao; Wang, Siyang; Tan, Liguo; Liu, Yue; Jiang, Chaofan; Zhao, Xing; Ding, Liming; Yi, Chenyi
Abstract: As a deep level trap in perovskite, metallic lead (Pb 0 ) greatly deteriorates the performances of perovskite optoelectronics such as perovskite solar cells. Here, we designed 2-trifluoromethyl-phenylethylamine hydroiodide (2-CF3 -PEAI) to serve as a multifunctional trap deactivating reagent which can react with metallic lead to eliminate deep level Pb 0 traps, forming a thin layer of 2D perovskite (2-CF3 -PEA)2 PbI4 atop the 3D perovskite without impediment of charge carrier transport. Moreover, functional groups in 2-CF3 -PEAI can deactivate a variety of traps in perovskite by multiple interactions, i.e. coordination between I - and Pb 2+, hydrogen bond between CF3 and formamidine, ionic interaction between NH3 + group and lead halide anion etc. Thus, non-radiative recombination was dramatically inhibited. The surface coverage of hydrophobic thin 2D perovskite (2-CF3 -PEA)2 PbI4 layer impedes the diffusion of metal (from anode) and humidity (from the environment) to 3D perovskite, leading to improved device stabilities. As a result, a 23.17% power conversion efficiency was achieved and an enhanced T 80 (~850 h) was obtained under continuous light-soaking without encapsulation, 121 times longer than that of the untreated devices. Graphical Abstract: ga1 Highlights: 2-trifluoromethyl-phenylethylamine hydroiodide was designed as a trap deactivator for perovskite solar cells. Deep level trap Pb 0 was scavenged and a thin 2D hydrophobic overlayer formed spontaneously. The power conversion efficiency raised from 21.77% to 23.17% after treatment. The treated device showed a T80 of 850 h under continuous light soaking without encapsulation.